PENGARUH LATIHAN CIRCUIT TRAINING UNTUK MENINGKATKAN KESEGARAN JASMANI ATLIT PENCAK SILAT USIA DINI (9-12 TAHUN) DI PERGURUAN TAPAK SUCI GELANGGANG SD MUHAMMADIYAH 18 MEDAN - Dede Pebriandi Sihotang; Novita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The purpose of this study was to determine whether or not circuit training had an effect on improving the physical fitness of early age pencak silat athletes (9-12 years) at tapak suci arena college, sd muhammadiyah 18 medan. This research was conducted at the muhammadiyah 18 elementary school medan. This research was started from 14 november to 26 december. This research is an experimental research with one group pretest-posttest design research method. The subjects of this study were early age of martial arts athletes (9-12 years) at the tapak suci arena college, sd muhammadiyah 18 medan, totaling 20 athletes. The instrument used was the tkji (indonesian physical fitness test), including the straight jumping test, bending elbow test, sitting-down test, 40-meter running test, 600-meter running test. The data analysis technique used t-test at a significant level of α = 0.05. The results of the research on the effect of circuit training on improving the physical fitness of early age pencak silat athletes (9-12 years) at Tapak Suci Gelanggang college, SD Muhammadiyah 18 Medan. From the analysis of the results of the data that has been carried out by statistical tests, it is obtained t-count of 111.8. Furthermore, this value is compared with the t-table value with dk = n-1 (20-1 = 19) at the significant level α = 0.05 is 2.09, thus t-count> t-table (111.8> 2.09) can be concluded that through Application of Circuit Training training can improve physical fitness in early childhood pencak silat (9-12 years) at Tapak Suci College arena, SD Muhammadiyah 18 Medan in 2020. These results are interpreted as accepted, so the hypothesis states there is an effect of circuit training training on improving athlete's physical fitness. Early childhood martial arts (9-12 years) at the Tapak Suci college arena, Muhammadiyah 18 Elementary School, Medan..